2012
DOI: 10.1139/z2012-086
|View full text |Cite
|
Sign up to set email alerts
|

Variation in diet of Semipalmated Sandpipers (Calidris pusilla) during stopover in the upper Bay of Fundy, Canada

Abstract: Semipalmated Sandpipers ( Calidris pusilla (L., 1766)) use the upper Bay of Fundy, Canada, as a critical stopover site during their annual fall migration to wintering grounds in South America. While in the area, they feed extensively on mudflat invertebrates. Historically the amphipod Corophium volutator (Pallas, 1766) has been thought to make up the majority of their diet. However, we have recently observed flexibility in foraging behaviour and prey selection by sandpipers. The extent of this flexibility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 48 publications
3
43
0
Order By: Relevance
“…FA levels in C. volutator in our study correspond well with those found in previous work (Ackman et al 1979;Maillet and Weber 2006), suggesting that these animals are a consistent source of essential FAs in the Bay of Fundy. Given recent evidence that Semipalmated Sandpipers in the region consume a broad diet (MacDonald et al 2012;Quinn and Hamilton 2012;Gerwing et al 2016), FA concentrations and profiles of alternate food items, relative to C. volutator, should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…FA levels in C. volutator in our study correspond well with those found in previous work (Ackman et al 1979;Maillet and Weber 2006), suggesting that these animals are a consistent source of essential FAs in the Bay of Fundy. Given recent evidence that Semipalmated Sandpipers in the region consume a broad diet (MacDonald et al 2012;Quinn and Hamilton 2012;Gerwing et al 2016), FA concentrations and profiles of alternate food items, relative to C. volutator, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Information on relative abundance of the different taxa at each site is provided in Gerwing et al (2015). We collected biofilm by scraping it from the surface in areas in which it was visible (appearing as a thin green or green-brown mat on the surface of the mud) using a thin spatula and stored it in scintillation vials (Quinn and Hamilton 2012). Some sediment was unavoidably collected with the biofilm, but this was minimized as much as possible, and birds are also known to consume considerable sediment while feeding (Reeder 1951) so what was sampled likely resembles what birds would consume.…”
Section: Food Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shorebirds detect prey by visual and tactile sensory mechanisms, been pecking and probing the main methods (Baker & Baker 1973), and flexible foraging strategies that can shift their diet to exploit locally abundant invertebrate resources (Skagen & Oman 1996, Quinn & Hamilton 2012. During nonbreeding seasons many shorebirds often forage across flats following tidal exposure and generally distribute themselves on specific habitats based on availability, distribution and abundance of macrobenthic invertebrates (Wilson 1990, Colwell & Landrum 1993, Butler et al 2001, according to the physical characteristics of tidal flats (Yates et al 1993, Colwell 1993, Finn et al 2008.…”
Section: Introductionmentioning
confidence: 99%